Moving on, moving back or changing it here and now: Self-revision in student translation processes from L2 and L3 - Antunović, Goranka (Array, 2011)
The paper aims to investigate student translation processes from the second and third language (L2 and L3), with particular regard to self-revision. The authors report on a study conducted to test the following two hypotheses: a) The distribution of student self-revisions, i.e. in which phase of the process they occur, is primarily related to individual working habits and not to language pair ; b) The type and quantity of self-revisions primarily depend on whether the student is working from his/her L2 or L3. The study is designed as a series of experiments involving students translating comparable texts (two sections of the same text produced by an EU institution of which multiple language versions exist) from their L2 (English) and L3 (Swedish) into their first language (Croatian). The processes are recorded with the help of a keystroke logging program (Translog). The type, number and distribution of self-revisions are analyzed. The findings suggest that the distribution of revisions over the phases may indeed be related to individual subjects’ habitual behavior. With regard to the expectation that the type and quantity of self-revisions primarily depend on SL competence, the findings do not provide a consistent picture.